Tightening the constraints on the mass distribution of the Frontier Fields MACSJ0416.1-2403 with VLT/MUSE spectroscopy. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Clément, Benjamin; Richard, Johan; Mahler, Guillaume; Patrício, Vera; Lagattuta, David
Abstract: We have combined the performances of the VLT/MUSE spectrograph together with the power of gravitational lensing by Frontier Fields galaxy clusters to offer a unique magnified view of the distant universe. The large field of view over a wide optical wavelength domain enables redshift measurements of numerous lensed galaxies in the cluster core. Spectroscopically-confirmed multiple-imaged systems are further used as strong constraints to improve the cluster mass model. Here, we focus on the galaxy cluster MACSJ0416.1-2403 and compare the revised magnification map with results from previous analysis.